Development of a new controller for solar home system: PWM charge controller & DC to DC converter (12V to 120V) / Mohammad Shariful Islam, Hasmaini Mohamad and S.Z. Mohammad Noor - Islam, Mohammad Shariful; Mohamad, Hasmaini; Mohammad Noor, S.Z. (UiTM Press, 2022)
Solar Home System (SHS) is a stand-alone power solution in isolated places where there is no connectivity to the national power grid. Currently, an off-grid SHS has a solar panel, a lead-acid battery, a Pulse Width Modulation (PWM) solar charge controller, and 12V DC power operated electrical home appliances; in some cases, a DC to DC converter or a DC to AC inverter has been connected. So far, various SHS packages have been introduced, each with a set of product features and prices. Since the majority of SHS are small in size, producing energy is inadequate to satisfy the customer's demand. This study introduces a new feature that incorporates both analog PWM solar charging techniques and a DC to DC (12V to 120V) converter to satisfy the needs of existing off-grid SHS users. The design of solar charging includes improved charging techniques i.e surge voltage and lightning protection. The result produced is a noisefree switching gate drive signal and high-performance fixedfrequency current mode controllers. The new controller's design also reduces the number of devices in the SHS; thus reduces the controller's total production cost.